Optimisation of sintering factors of titanium foams using taguchi method - Ahmad, S. (Penerbit UTHM, 2010)
Metal foams have the potential to be used in the production of bipolar plates in Polymer Electron Membrane Fuel Cells (PEMFC). In this paper, pure titanium was used to prepare titanium foam using the slurry method. The electrical conductivity is the most important parameter to be considered in the production of good bipolar plates. To achieve a high conductivity of the titanium foam, the effects of various parameters including temperature, time profile and composition have to be characterised and optimised. This paper reports the use of the Taguchi method in optimising the processing parameters of pure titanium foams. The effects of four sintering factors, namely, composition, sintering temperature, heating rate and soaking time on the electrical conductivity has been studied. The titanium slurry was prepared by mixing titanium alloy powder, polyethylene glycol (PEG), methylcellulose and water. Polyurethane (PU) foams were then impregnated into the slurry and later dried at room temperature. These were next sintered in a high temperature vacuum furnace. The various factors were assigned to an L9 orthogonal array. From the Analysis of Variance (ANOVA), the composition of titanium powder has the highest percentage of contribution (24.51) to the electrical conductivity followed by the heating rate (10.29). The optimum electrical conductivity was found to be 1336.227 ± 240.61 S/cm-1 for this titanium foam. It was achieved with a 70% composition of titanium, sintering temperature of 1200oC, a heating rate of 0.5oC/min and 2 hours soaking time. Confirmatory experiments have produced results that lay within the 90% confidence interval.